A RECONNAISSANCE 40AR 39AR GEOCHRONOLOGIC STUDY OF ORE-BEARING AND RELATED ROCKS, SIBERIAN RUSSIA - Brent Dalrymple G.; Czamanske G.K.; Lanphere M.A.; Fedorenko V.A.; Likhachev A.P.; Simonov O.N. (My University, 1995)
age spectra of biotite from a mineralized vein in the ore-bearing, Noril'sk I intrusion and from picritic-like gabbrodolerite from the weakly mineralized, Lower Talnakh intrusion show that these bodies were emplaced at 249 ± 2 Ma, which is not significantly different from the age of the Permian-Triassic boundary. The ore-bearing intrusions postdate the lower third of the flood-basalt sequence in the Noril'sk area and, on the basis of geochemistry, can best be correlated with lavas slightly younger than those which they cut. Thus, flood basalt was erupted at the time of the Permian-Triassic mass extinction event, although its role in this event is, as yet, ill defined.Additional new age data for a group of intrusive and extrusive rocks on the western margin of the Siberian craton indicate that mafic magmatism extended over a period of several tens of million years, whereas paleomagnetic data suggest that the bulk of the Siberian flood-basalt sequence near Noril'sk has been erupted in only a million years or so. ages of plagioclase from early flood-basalt flows are about 2% younger than those obtained for biotite from the crosscutting, Noril'sk I intrusion, probably because of slight alteration and Argon loss from the plagioclase.
Keywords: Permian; Triassic; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая; Палеозой::Пермская